A microprobe study of tephra glasses from the Fjallsendahraun lava, central Iceland - Ingibjörg Þórðardóttir 1997- (2020)
The ∼1362 A.D Fjallsendahraun lava in central Iceland originates from the Bárðarbunga volcanic system. Bárðarbunga is one of the youngest and most active volcanic system in Iceland with over 20 known basaltic eruptions in historical time. In this study, major element analysis of 16 glassy tephra samples from recent basaltic fissure eruptions which all originated within the Bárðarbunga system are presented. The samples come from Fjallsendahraun (11), Tjörvahraun (1), Tröllahraun (2), Vatnaöldur (1) and Veiðivötn (1). Additional datasets from four other localities, including the recent 2014-15 Holuhraun, are used for comparison. All sample localities apart from Tjörvahraun are basaltic in composition and display compositions typical for fissure lavas erupted in central Iceland. Fjallsendahraun is compositionally indistinguishable from other historical basalts from the Bárðarbunga volcanic system, suggesting that these lava units all originate from a shared mid-crustal magma body. Furthermore, the estimated pressure (or depth) of this suggested magma body is ∼1,8 kbar. Fjallsendahraun (∼1362 e.kr) er staðsett vestan við Öskju á mið-Íslandi og á uppruna sinn að rekja til megineldstöðvarinnar Bárðarbungu. Bárðarbunga er ein elsta og virkasta megineldstöð Íslands og hefur framkvæmt rúmlega 20 flæðigos á sögulegum tíma. Þessi rannsókn inniheldur efnagreiningar á aðalefnum úr 16 glersýnum frá Fjallsendahrauni (11), Tjörvahrauni (1), Tröllahrauni (2), Vatnaöldum (1) og Veiðivötnum (1). Hraunin eru tiltölulega nýleg og með sameiginlegan uppruna í Bárðarbungu. Að auki eru efnagreiningar frá fjórum öðrum hraun- og gjóskueiningum notaðar til samanburðar, meðal annars Holuhraun 2014-15. Allar hrauneiningarnar fyrir utan Tjörvahraun eru basískar með dæmigerða efnasamsetningu fyrir flæðigos á mið-Íslandi. Fjallsendahraun er efnafræðilega óaðgreinanlegt frá öðrum sögulegum hrauneiningum úr Bárðarbungu sem bendir til þess að hraunin eiga sameiginlegan uppruna í frumstæðan kvikugeymi í miðri skorpunni. Ályktaður þrýstingur (eða ...